(untitled) (REMUNOM, 2026)
This study presents, in a systematic and didactic manner, the development and validation of a three-dimensional finite element model in the linear elastic regime for timber–concrete composite T-beams, implemented in Abaqus. Glued laminated timber was modeled as a fully orthotropic material, with explicit definition of elastic constants in the longitudinal, radial, and tangential directions, and proper tensor transformation to the global structural coordinate system. Concrete was represented as a homogeneous isotropic material in the pre-cracking elastic range. The numerical model was calibrated and validated against experimental results available in the literature, considering the linear portion of the load–displacement response up to 100 kN, a range in which no plasticity, significant cracking, or interface degradation was observed. After validation, a comparative analysis was conducted by replacing the timber species and concrete class to evaluate their influence on the global stiffness of the composite system. The results demonstrate that the initial stiffness of the composite beam is predominantly governed by the longitudinal modulus of elasticity of the timber, while increasing the concrete strength class provides comparatively limited gains in elastic stiffness. The study highlights the structural relevance of orthotropic material modeling and emphasizes the potential of Brazilian timber species for application in hybrid timber–concrete structural systems.